Factors Affecting the Lime Requirement in Acidic Inceptisols of Jharkhand - Bhowmick, Ritabrata; Mandal, Jajati; Mandal, Nintu (International Journal of Bio-resource and Stress Management, 2016)
Perhaps the most outstanding features of the soil solution are its reaction i.e. whether it is acidic or alkaline or neutral. Acid soils are problematic soils because of the fact that soil acidity is a serious threat to profitable crop production and lime is essential for correlation of acidity as well as of toxic and infertile condition likely to be prevalent in the acid soils. A considerable amount of work is necessary to define the optimum pH range for the principle crops and rotation systems practiced in the state, to measure the yield responses to be expected for the more important soil types and to determine the longevity of the lime response. Adsorbed cations, Hydrogen (H+) and Aluminium (Al3+) are largely responsible for soil acidity. The present study was conducted in the Department of Chemistry, Techno India, Batanagar in the year 2015 to determine the Lime Requirement (LR) of acid soils collected from three soil series of Jamtara district of Jharkhand viz., Kunjabana (I), Bhandarbera and Kunjabana (II). In order to determine the LR, the soils were incubated with different doses of lime (Calcium Carbonate) and the result obtained was in the following order: Kunjabana I>Kunjabana II>Bhandarbera. The lime requirement showed significant correlation with pH (H2O) (r=-0.69), pH (KCl) (r=-0.59), clay content (r=-0.53), organic matter (r=0.65), the product of the increase in pH value due to liming and organic matter (r=0.71), CEC (r=0.63), log CEC (r=0.65), AlKCl (r=0.71), FeNH4OAc(r=0.65), AlNH4OAc (r=0.59), total potential acidity (r=0.52) and lime potential (r=-0.84).